Functional annotation and complete genome analysis confirm the probiotic characteristics of Bacillus species isolated from the gut of Nile tilapia. (15th June 2022) - Kuebutornye, Felix Kofi Agbeko; Lu, Yishan; Wang, Zhiwen; Mraz, Jan
Abstract: Bacillus velezensis TPS3N, Bacillus subtilis TPS4, and Bacillus amyloliquefaciens TPS17 showing probiotic traits were isolated from the gut of Nile tilapia. However, the genetic information of these strains is obscure. Therefore, the current investigation was undertaken to prove the probiotic traits of B. velezensis TPS3N, B. subtilis TPS4, and B. amyloliquefaciens TPS17 through genomic analysis. Genome mining revealed gene clusters responsible for acid and bile (stress) tolerance as well as adhesion and colonization of the host's gut. Gene markers coding for a wide range of bacteriocins and secondary metabolites were also identified in the genome of the three isolates, suggesting that the three isolates could be used in place of traditional antibiotics. Genomic analysis also showed that the three isolates could boost the host's immunity and help digest complex feed ingredients by secreting numerous useful enzymes. Putative genes responsible for the synthesis of 6 vitamins and 11 amino acids (essential and non-essential) were found in the genome of the three isolates; coupled with their enzymatic capacity showed they could also be useful in other industrial applications. The current study provides a better understanding of the three isolates and provides an avenue for enhancing these strains through genetic manipulations. Graphical abstract: Image 1 Highlights: TPS3N, TPS4, and TPS17 from Nile tilapia showed probiotic traits in vivo and in vitro . Gene clusters responsible for stress tolerance were detected in the genome of the three isolates. Genome mining revealed gene clusters coding for secondary metabolites and other useful enzymes. Putative genes for vitamins and amino acids synthesis were found in the isolates' genome. Genome analysis confirm the probiotic traits of the three isolates.